2002
DOI: 10.1210/jc.2002-020561
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Plasma Protein A Proteolytic Activity Is Associated with the Human Placental Trophoblast Cell Membrane

Abstract: Pregnancy-associated plasma protein-A (PAPP-A) is a product of the placenta and decidua and is secreted into the maternal circulation during human pregnancy. It recently has been identified as an IGF binding protein (IGFBP)-4 protease. Presumed functions at the maternal-fetal interface are to proteolyze IGFBP-4 and thus increase IGF bioavailability locally in the placenta, to promote IGF-II-mediated trophoblast invasion into the maternal decidua, and to modulate IGF regulation of steroidogenesis and glucose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…2). Genes abundantly expressed in villus regions of placenta relative to other normal human tissues included insulin-like growth factor (IGF) 2 and pregnancy-associated plasma protein A (PAPP-A), which are known to be expressed in placenta (16,17). In some cases, the extraplacental expression would suggest a potential biological role.…”
Section: Resultsmentioning
confidence: 99%
“…2). Genes abundantly expressed in villus regions of placenta relative to other normal human tissues included insulin-like growth factor (IGF) 2 and pregnancy-associated plasma protein A (PAPP-A), which are known to be expressed in placenta (16,17). In some cases, the extraplacental expression would suggest a potential biological role.…”
Section: Resultsmentioning
confidence: 99%
“…IGFBPs are expressed by the maternal decidua and may regulate IGF actions during pregnancy (Han et al 1996). In this context IGFBP-4 is particularly interesting for several reasons: (i) IGFBP-4 is the second most abundant IGFBP in the placental bed (Han et al 1996); (ii) PAPP-A, an IGF-dependent IGFBP-4 protease, is secreted by human trophoblast cells and decidualized endometrial stroma , Sun et al 2002 and is markedly increased in the maternal circulation as pregnancy progresses (Byun et al 2000); and (iii) in human pregnancy serum the majority of PAPP-A (.99%) is found as a PAPP-A/proMBP complex (Oxvig et al 1993). During pregnancy, rapid placental development and fetal growth obviously increases the need for growth-promoting factors such as IGFs.…”
Section: Reproductive Physiologymentioning
confidence: 99%
“…Although these data were carried out with polyspecific PAPP-A antibodies known to recognize different antigens (22,38), they are in agreement with our data. Furthermore, we have recently demonstrated that PAPP-A antigen present in a preparation of solubilized membranes from human trophoblasts is proteolytically active (51).…”
Section: Papp-a Complexed To Prombp Does Notmentioning
confidence: 99%